INTERNATIONAL EXPERIENCE IN USING DIGITAL EXTENSIVE READING TOOLS IN FOREIGN LANGUAGE EDUCATION - Rakhmonova Munirabonu G‘ulomjon qizi; Samatova Barnokhon Ravshanxanovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article analyzes international experience in using digital extensive reading tools in foreign language education. The integration of digital technologies into the learning process helps increase students’ motivation to read, develop independent learning skills, and improve overall language competence. The study highlights the role of digital platforms and resources in developing reading skills, vocabulary, and critical thinking. The findings indicate that digital extensive reading tools can significantly enhance the effectiveness of foreign language learning.